Analisis Laporan Keuangan Syariah – PT Bank Muamalat Indonesia Tbk - Justin Justin; Padli Rahman; Aurelia Priscilla Cuandra; Serena Phang; Viandi Agustinus; Gary Gary (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2023)
PT Bank Muamalat Indonesia Tbk (BMI) became a pioneer of Islamic banking in Indonesia after the 1997-1998 monetary crisis. Established in 1992, BMI continues to innovate with Islamic financial products, such as Mudharabah Subordinated Sukuk and Shar-e as the first instant savings product in Indonesia. BMI’s focus is not only on customer service, but also on green banking with a policy of not financing businesses that harm the environment. With this, the focus of this research is to analyze the products offered by BMI from 2020 to 2022. Data is obtained through the company’s annual financial statements. The performance of this bank is also proven to be in accordance with existing sharia regulations. However, it also has shortcomings in the transparency of the company.